2001
DOI: 10.1039/b008184l
|View full text |Cite
|
Sign up to set email alerts
|

Mild and efficient methodology for installation of gem-diallyl functionality on carbohydrate synthons

Abstract: A versatile approach to construct gem-diallyl functionality has been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The crucial reaction, i.e., transformation of 8 to the diallyl compound 9 was achieved by treating it with allyltributylstannane, catalytic AIBN in refluxing benzene in an overall yield of 43%. 5 The 1 H-and 13 C-NMR spectra of the diallyl compound 9 were as expected and only half of the signals were seen. 10b Following the similar protocol of de Meijere and co-workers that has been used in the synthesis of 1, 2 cyclopropanation of the diallyl compound 9 was succesfully achieved by treating 9 with an excess ethereal solution of diazomethane in the presence of catalytic Pd(OAc) 2 , 9 and the tetracyclopropyl derivative 3 was obtained in good yield.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…The crucial reaction, i.e., transformation of 8 to the diallyl compound 9 was achieved by treating it with allyltributylstannane, catalytic AIBN in refluxing benzene in an overall yield of 43%. 5 The 1 H-and 13 C-NMR spectra of the diallyl compound 9 were as expected and only half of the signals were seen. 10b Following the similar protocol of de Meijere and co-workers that has been used in the synthesis of 1, 2 cyclopropanation of the diallyl compound 9 was succesfully achieved by treating 9 with an excess ethereal solution of diazomethane in the presence of catalytic Pd(OAc) 2 , 9 and the tetracyclopropyl derivative 3 was obtained in good yield.…”
supporting
confidence: 63%
“…This communication describes the synthesis of tetrakis(cyclopropylmethyl)methane (3) and its solid state structure. The planned synthesis of 3 consists of an exquisite application of our gem-diallylation approach 5 for the synthesis of the diallyl derivative 9, and subsequent twofold cyclopropanation of 9. The synthesis commenced from the dicyclopropyl acetone (4) which was made according to the known procedure.…”
mentioning
confidence: 99%
“…1 and catalytic AIBN to give the gem-diallyl derivative 5 in 76% yield (Scheme 2). The structure of 5 was proven, beyond any doubt, by 1 H, 13 C, mass spectroscopy and elemental analysis.…”
Section: Resultsmentioning
confidence: 94%
“…58 In 2001, Gurjar et al reported the preparation of carbohydrate synthons possessing gem-diallyl functionality. 59 One of these synthons (171) was also closed by RCM to provide spiro compound 172 in 80% yield (Scheme 25). 1 N H C l , T H F 2 5 ° C , 2 h 2 .…”
Section: Ring-closing Metathesismentioning
confidence: 99%